SINTESIS KARBON BERPORI BERBASIS DAUN JERUK NIPIS (Citrus Aurentifolia S.) SEBAGAI MATERIAL ELEKTRODA UNTUK APLIKASI SUPERKAPASITOR - Erman Taer; Melda Riyani Butet; Apriwandi Apriwandi; Rika Taslim (Komunikasi Fisika Indonesia, 2023)
In this study, the electrode material was successfully made from activated carbon based on lime leaf biomass with variations in physical activation temperature of 800 ˚C, 850 ˚C, and 900 ˚C for supercapacitor applications. Porous carbon was synthesized through pre-carbonization steps, chemical activation using ZnCl2 activator, carbonization using N2 gas at a temperature of 600 ˚C, and physical activation using CO2. Density analysis confirmed the potential for the DJN-850 sample to have a high shrinkage of 52.24%. X-ray diffraction shows an amorphous structure of carbon characterized by broading peaks at 2θ=22° and 24°. Scanning electron microscopy analysis performed that the optimized sample possessed rich meso-,macropores followed by a high carbon content of 90.25%. The Fourier spectroscopic transformation test results identified the presence of functional groups O-H, C-O, C-H, C=C, and C≡C in the sample. The precursor activated at 850 C possessed a specific surface area of 675.129 m2 g-1 with adjusting micro-mesopore. Furthermore, the electrochemical properties of the samples were measured using cyclic voltammetry and galvanostatic charge-discharge with specific capacitances of 144.14 F g-1 and 189 F g-1, respectively.. Keywords: biomass precursor; Citrus aurentifolia S., carbon porous, electrode material, supercapacitor